George Gershwin : his life and work - Pollack, Howard (Berkeley : University of California Press, 2006)
This comprehensive biography of George Gershwin unravels the myths surrounding one of America's most celebrated composers and establishes the enduring value of his music. Gershwin created some of the most beloved music of the twentieth century and helped make the golden age of Broadway. Biographer Pollack draws from sketches, manuscripts, letters, interviews, books, articles, recordings, films, and other materials to create an expansive, lively chronicle. He describes Gershwin's family, childhood, and education; his early career as a pianist; his friendships and romantic life; his relation to various musical trends; his writings on music; his working methods; and his tragic death at the age of 38. He also surveys Gershwin's entire oeuvre, from his first surviving compositions to the melodies that his brother and principal collaborator, Ira Gershwin, lyricized after his death. Pollack concludes with a perceptive consideration of the important role Gershwin's music plays in our own time.--From publisher description.
Delicious and the Second rhapsody (1931) -- Of thee I sing (1931) -- George Gershwin's song-book (1932) -- The Cuban overture (1932) and Pardon my English (1933) -- Let 'em eat cake (1933) and Variations on "I got rhythm" (1934) -- Porgy and Bess (1935) -- The first production of Porgy and Bess -- Porgy and Bess in revival -- Porgy and Bess on disc, film, and the concert stage -- From Swing is king (1936) to A damsel in distress (1937) -- From The Goldwyn follies (1938) to Kiss me, stupid (1964) -- Conclusion.
Includes bibliographical references (p. 817-824) and index.
Keywords: Gershwin, George, -- 1898-1937.; Composers -- United States -- Biography; Gershwin, George, -- 1898-1937.; Compositeurs -- v; Gershwin, George, -- (1898-1937); Gershwin, George, -- 1898-1937.; Composers; United States; Biography